Pengembangan Media Lift the Flap Book Pengenalan Bilangan untuk Anak Usia Dini - Delfiana, Mareta; Setyadi, Danang (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
Introducing numbers to early childhood is essential to build a foundation for logical thinking and problem-solving skills that will be used throughout their lives. This study developed an interactive learning medium in the form of a Lift the Flap Book Mengenal Bilangan 1–10 to help early childhood learners recognize numbers from 1 to 10. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The trial involved one teacher and five parents from TK Kanisius Genuk, as well as one teacher and five parents from TK PGRI Baran. Data were collected through expert validation of the content and media, and practicality tests using questionnaires administered to teachers and parents. During the implementation phase, the media was used on a limited basis in early childhood classes to observe children’s responses and the ease of use by teachers. Evaluation was conducted by collecting feedback from teachers and parents regarding their experience using the media during learning. The validation results indicated a feasibility score of 90.5%, while the practicality test achieved a score of 91%, suggesting that the media is both valid and practical for teaching number recognition to early childhood learners. This research produced an innovative learning medium that effectively supports an engaging learning process for children.